Methylisothiazolinone and benzisothiazolinone are widely used in paint: a multicentre study of paints from five European countries - Schwensen, Jakob F.; Lundov, Michael D.; Bossi, Rossana; Banerjee, Piu; Gimenez-Arnau, Elena; Lepoittevin, Jean-Pierre; Liden, Carola; Uter, Wolfgang; Yazar, Kerem; White, Ian R.; Johansen, Jeanne D. (Contact Dermatitis, 2015)
In view of the current epidemic of contact allergy to methylisothiazolinone (MI), it is important to clarify the extent of use of MI and related isothiazolinones in paints currently available for the consumer and worker in Europe.To elucidate the use and concentrations of MI, methylchloroisothiazolinone (MCI) and benzisothiazolinone (BIT) in paints on the European retail market.Wall paints (n = 71) were randomly purchased in retail outlets in five European countries. The paints were quantitatively analysed for their contents of MI, MCI and BIT by high-performance liquid chromatography coupled to tandem mass spectrometry.MI was found in 93.0% (n = 66) of the paints, with concentrations ranging from 0.7 to 180.9 ppm, MCI in 23.9% (n = 17), ranging from 0.26 to 11.4 ppm, and BIT in 95.8% (n = 68), ranging from 0.1 to 462.5 ppm. High concentrations of MI were found in paints from all five countries. Paints purchased in Denmark and Sweden contained especially high concentrations of BIT.The use of MI across European countries is extensive. In view of the ongoing epidemic of MI contact allergy, an evaluation of the safety of MI in paints is needed.
EVALuna2:5462